Developing a list of important drug- drug interactions in the clinical practice in the internal department – Kien An Hospital, Hai Phong City - Hanh, Nguyen Thi; Thi Phuong Thao, Vu; Quang Tuan, Ha; Xuan Bach, Nguyen; Thanh Hai, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2019)
This study was aimed to develop a list of important drug- drug interactions (DDIs) at the Internal department – Kien An Hospital. Subjects and methods : This study was 3 phases: (1) The construction of the initiative list was based on consenous of the documentations from the list of drugs in Kien An hospital: Micromedex 2.0, the patient leaflets and Drug Interaction Fact 2014. (2) The research group reviewed all the in-patient medical records in the General internal department and Cardiology department and sorted the high-frequency DDIs with prevalance higher than 1%. (3) After the DDIs of the first list and the second list were assessed by a group of doctors and pharmacists who the proposed a list of important DDIs at the internal deparment – Kien An Hospital. Results : From the documentations, the research group constructed 27 DDIs of the list. Conclusion : This DDIs list can be disseminated in clinical departments and integrated into the prescribing software of Kien An hospital. Keywords Kien An hospital, DDIs, Micromedex 2.0, high-frequency. References [1] D.C. Malone, J. Abarca, P.D. Hansten, A.J. Grizzle, E.P. Armstrong, R.C.V Bergen, B.S. Duncan-Edgar, S.L. Solomon, R.B. Lipton, Indentification of Serious Drug-Drug Interactions: Results of the Partnership to Prevent Drug-Drug Interactions, J. Am. Pharm. Assoc. 44 (2004) 142-151. https://doi.org/10.1331/154434504773062591. [2] P. Vonbach, A. Dubied, S. Kra¨henbu¨hl, J.H. Beer, Evaluation of frequently used drug interaction screening programs, Pharm. World. Sci. 30 (2008) 367-374. https://doi.org/10.1007/s11096-008-9191-x. [3] A.J. Harman, S.J. Press, Collecting and Analyzing Expert Group Judgement Data, Rand Corporation, Califonia, 1975. [4] P.E. Shrout, J.L. Fleiss, Intraclass Correlations: Uses in Assessing Rater Reliability, Psychol Bull. 86 (1979) 420-442. https://doi.org/10.1037//0033-2909.86.2.420. [5] D.S. Tatro, Drug Interaction Facts, Wolters Kluwer Health, 2014. [6] J. Abarca, D.C. Malone, E.P. Armstrong, A.J. Grizzle, P.D. Hansten, R.C.V. Bergen, R.B. Lipton, Concordance of Severity Ratings Provided in Four Drug Interaction Compendia, J. Am. Pharm. Assoc. 44 (2004) 136-141. https://doi.org/10.1331/154434504773062582. [7] N.T. Hang, P.T. Ha, N.M. Hoa, T.T. Ngan, N.H, Anh, N.T.H. Ha, Developing a list of clinically significant drug-drug interactions at the National Hospital of Pediatrics, Journal of Pharmaceutical reseach and Drug information 4+5 (2016) 137-141 (in Vietnamese). [8] Pharmacy Times, Diuretics, ACEIs, ARBs and NSAIDs: A Nephrotoxic Combination. https://www.pharmacytimes.com/publications/issue/2013/april2013/diuretics-aceis-arbs-and-nsaids-a-nephrotoxic-combination (accessed 18 April 2013).